Prevalence of alcohol abuse and associated factors in a population-based study Prevalência da dependência de álcool e fatores associados em estudo de base populacional - Marilisa Berti de Azevedo Barros; Neury José Botega; Paulo Dalgalarrondo; Letícia Marín-León; Helenice Bosco de Oliveira (Universidade de São Paulo, 2007)
OBJECTIVE: To estimate the prevalence of alcohol abuse/dependence and identify associated factors among demographic, family, socioeconomic and mental health variables. METHODS: A household survey was carried out in the urban area of Campinas, southeastern Brazil, in 2003. A total of 515 subjects, aged 14 years or more were randomly selected using a stratified cluster sample. The Self-Report Questionnaire and the Alcohol Use Disorder Identification Test were used in the interview. Prevalences were calculated, and univariate and multivariate logistic analyses performed by estimating odds ratios and 95% confidence intervals. RESULTS: The estimated prevalence of alcohol abuse/dependence was 13.1% (95% CI: 8.4;19.9) in men and 4.1% (95% CI: 1.9;8.6) in women. In the final multiple logistic regression model, alcohol abuse/dependence was significantly associated with age, income, schooling, religion and illicit drug use. The adjusted odds ratios were significantly higher in following variables: income between 2,501 and 10,000 dollars (OR=10.29); income above 10,000 dollars (OR=10.20); less than 12 years of schooling (OR=13.42); no religion (OR=9.16) or religion other than Evangelical (OR=4.77); and illicit drug use during lifetime (OR=4.47). Alcohol abuse and dependence patterns were different according to age group. CONCLUSIONS: There is a significantly high prevalence of alcohol abuse/dependence in this population. The knowledge of factors associated with alcohol abuse, and differences in consumption patterns should be taken into account in the development of harm reduction strategies. OBJETIVO: Estimar a prevalência do abuso/dependência de álcool e identificar fatores associados entre variáveis demográficas, familiares, socioeconômicas e relativas à saúde mental. MÉTODOS: Inquérito domiciliar na área urbana de Campinas, Estado de São Paulo, realizado em 2003. Indivíduos de 14 anos ou mais de idade (N=515) foram selecionados aleatoriamente, mediante amostragem estratificada por conglomerados e avaliados por entrevista com as escalas Self-Report Questionnaire e o Alcohol Use Disorder Identification Test. Foram calculadas as prevalências e realizadas análises logísticas uni e multivariada, razões de chance e intervalos de confiança. RESULTADOS: As prevalências estimadas de abuso/dependência de álcool foram 13,1% (IC 95%: 8,4%;19,9%) nos homens e 4,1% (IC 95%: 1,9%;8,6%) nas mulheres. No modelo de regressão logística múltipla final, o abuso/dependência de álcool revelou-se significativamente associado com idade, renda, escolaridade, religião e uso de drogas ilícitas. As categorias que apresentaram as maiores razões de chance ajustadas foram: renda (entre 2.501 e 10.000 dólares, OR=10,29; superior a 10.000 dólares, OR=10,20), escolaridade inferior a 12 anos (OR=13,42), não ter religião (OR=9,16) ou ser de religião que não fosse a evangélica (OR=4,77) e ter usado drogas ilícitas em algum momento da vida (OR=4,47). Os padrões de consumo e de dependência diferenciaram-se segundo o grupo etário. CONCLUSÕES: A prevalência de uso abusivo/dependência de álcool na população é considerável. O conhecimento dos fatores associados a tal comportamento e das diferenças de padrão de consumo deve ser levado em consideração na elaboração de estratégias de redução do dano.